The Effectiveness of Single Shot Intravesical Chemotherapy with Mitomycin-C in Preventing Recurrence of Non-Muscle Invasive Bladder Cancer: Town Teaching Hospital, Peshawar - Rehman, Faiza -Ur-; Khattak, Bilal; Islam Nasir, Irfan -Ul-; Naeem, Muhammad (Journal of Gandhara Medical and Dental Science, 2016)
OBJECTIVES: To determine the efficacy of single dose intravesical chemotherapy with Mitomycin-C following transurethral resection of non-muscle invasive bladder cancer METHODS: It was a Descriptive case series study conducted in the admitted patients of bladder cancer in the institute of kidney disease, Peshawar within one year duration. Total of 128 patients were enrolled in the study. After TURBT patient were catheterized with 22 FR 3 ways foley’s catheter and urinary bladder irrigation was started with normal saline. Mitomycin 40 mg dissolved in 20 ml of normal saline was instilled once hematuria settles within 24 hours. All the patients were called back after 3 months for check cystoscopy and the findings were recorded so as to detect recurrence of bladder tumor RESULTS: In this study, 128 patients with transurethral resection of non-muscle invasive bladder cancer have been observed; male to female ratio was 5:1. The age ranges of patients were from 18 to 75 years. Average age was 51.13 years + 14.33SD. Recurrence was found in 20(15.62%) of cases while the remaining 108(84.38%) were free of recurrence. CONCLUSION: Our study confirmed the effectiveness of a single shot immediate Mitomycin-C instillation in patients with non-muscle-invasive bladder tumors.